Development of the first reference antibody panel for qualification and validation of cytokine release assay platforms – Report of an international collaborative study. Issue 4 (December 2020) - Vessillier, Sandrine; Fort, Madeline; O'Donnell, Lynn; Hinton, Heather; Nadwodny, Kimberly; Piccotti, Joseph; Rigsby, Peter; Staflin, Karin; Stebbings, Richard; Mekala, Divya; Willingham, Aarron; Wolf, Babette; et al.
Highlights: Cytokine release syndrome is a concern for novel antibody therapeutics. In vitro cytokine release assays are key for hazard identification. Positive and negative control antibodies generated for assay qualification. Control antibody panel induced cytokine release in a variety of assay platforms. Abstract: Immunomodulatory therapeutics such as monoclonal antibodies (mAb) carry an inherent risk of undesired immune reactions. One such risk is cytokine release syndrome (CRS), a rapid systemic inflammatory response characterized by the secretion of pro-inflammatory cytokines from immune cells. It is crucial for patient safety to correctly identify potential risk of CRS prior to first-in-human dose administration. For this purpose, a variety of in vitro cytokine release assays (CRA) are routinely used as part of the preclinical safety assessment of novel therapeutic mAbs. One of the challenges for the development and comparison of CRA performance is the lack of availability of standard positive and negative control mAbs for use in assay qualification. To address this issue, the National Institute for Biological Standards and Control (NIBSC) developed a reference panel of lyophilised mAbs known to induce CRS in the clinic: human anti-CD52, mouse anti-CD3 and human superagonistic (SA) anti-CD28 mAb manufactured according to the respective published sequences of Campath-1H® (alemtuzumab, IgG1), Orthoclone OKT-3® (muromonab, IgG2a) and TGN1412 (theralizumab, IgG4), as well as three isotype matched negative controls (human IgG1, mouse IgG2a and human IgG4, respectively). The relative capacity of these control mAbs to stimulate the release of IFN-γ, IL-2, TNF-α and IL-6 in vitro was evaluated in eleven laboratories in an international collaborative study mediated through the HESI Immuno-safety Technical Committee Cytokine Release Assay Working Group. Participants tested the NIBSC mAbs in a variety of CRA platforms established at each institution. This paper presents the results from the centralised cytokine quantification on all the plasma/supernatants corresponding to the stimulation of immune cells in the different CRA platforms by a single concentration of each mAb. Each positive control mAb induced significant cytokine release in most of the tested CRA platforms. There was a high inter-laboratory variability in the levels of cytokines produced, but similar patterns of response were observed across laboratories that replicated the cytokine release patterns previously published for the respective clinical therapeutic mAbs. Therefore, the positive and negative mAbs are suitable as a reference panel for the qualification and validation of CRAs, comparison of different CRA platforms (e.g. solid vs aqueous phase), and intra- and inter-laboratory comparison of CRA performance. Thus, the use of this panel of positive and negative control mAbs will increase the confidence in the robustness of a CRA platform to identify a potential CRS risk for novel immunomodulatory therapeutic candidates.